Cardiocerebral infarction. The current state of the problem (literature review) - Vladislav E. Ispavskii; Valerii S. Ermakov; Viacheslav N. Kravchuk; Vadim V. Dalinin (Clinical Medicine (Russian Journal), 2026)
Cardio-cerebral infarction (CCI), which refers to the simultaneous or sequential development of acute ischemic stroke and myocardial infarction, is a life-threatening condition with a high mortality rate. This review summarizes current data on the pathophysiology and management of CCI. The key mechanism behind CCI is systemic thromboembolism, which also increases the risk of COVID-19. Special attention is given to the complexity of selecting a reperfusion strategy, which requires a multidisciplinary approach. Analysis of clinical cases shows that combined endovascular intervention leads to better outcomes. However, further research is needed to develop unified treatment recommendations.